PENGEMBANGAN MEDIA BERBASIS ANDROID PADA MATA PELAJARAN DESAIN MULTIMEDIA INTERAKTIF (DMI) DI SMK NEGERI 1 SIJUNJUNG - M.Rafiq Fadhillah; Sofia Edriati; Ami Anggraini Samudra (Jurnal Informatika Kaputama (JIK), 2023)
The goal to be achieved in this study is to find out the valid and practical characteristics of the Interactive Multimedia Design subject at SMK Negeri 1 Sijunjung, the method used is Research and Development (R&D), while the development model used is the ADDIE development model, namely the development which consists of five stages, namely, Analysis (analysis), Design (design), Development (development), Implementation (implementation), and Evaluation (evaluation). Research on the development of the ADDIE model was carried out only up to the Development stage, because the purpose of this research was only limited to developing and producing a valid and practical learning media, to be implemented. Making learning media in this Android-based interactive multimedia design subject uses the MIT App Inventor. The validity test of this Android-based learning media was carried out by 3 validators, namely the media validator and the material validator, for the media validator it was carried out by 3 lecturers, while the material validation was carried out by 1 lecturer and 2 teachers who teach interactive multimedia design subjects at SMKN 1 Sijunjung. the validation results of media experts were 0.903% in the valid category and material experts were 0.859% in the valid category. Android-based learning media is declared valid. The practicality Test of Android-based learning media from teacher practicality data is 91.66% in the very practical category.